JAPAN AND INDONESIA COOPERATION IN DISASTER MANAGEMENT - Azmi Afiefa Azka (2013)

(untitled)
Currently, disaster management has been concerned as a major issue in this world. It is very important issue to be discussed for several countries. Such as, Japan and Indonesia, both countries considered disaster management. This undergraduate thesis discuss about Japan and Indonesia cooperation in disaster management. So, when Indonesia was hit by earthquake and tsunami, Japan gave many aids and assistances to victims. Then, it aimed to cooperation in disaster management. Both countries signed